The regulators of G protein signaling (RGS) domains of RGS4, RGS10, and GAIP retain GTPase activating protein activity in vitro - Popov, Serguei (The National Academy of Sciences of the USA, 1997)
Regulators of G protein signaling (RGS) proteins accelerate GTP hydrolysis by G(i) but not by G(s) class α-subunits. All RGS proteins share a conserved 120-amino acid sequence termed the RGS domain. We have demonstrated that the RGS domains of RGS4, RGS10, and GAIP retain GTPase accelerating activity with the G(i) class substrates G(iα1,) G(oα), and G(zα) in vitro. No regulatory activity of the RGS domains was detected for G(sα). Short deletions within the RGS domain of RGS4 destroyed GTPase activating protein activity and G(iα1) substrate binding. Comparable protein–protein interactions between G(iα1)–GDP–AlF(4)(−) and the RGS domain or full-length RGS4 were detected using surface plasmon resonance.